2020
DOI: 10.1186/s12903-020-01280-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of oral health promotion program for persons with severe mental illness: a cluster randomized controlled study

Abstract: Objective To evaluate the effectiveness of a composite oral health promotion program designed to reduce dental plaque among persons with severe mental illness in a psychiatric institution. Methods A cluster randomized controlled study was carried out in chronic psychiatric wards of a general hospital in central Taiwan. Sixty-eight eligible male individuals admitted to 2 wards were randomly assigned to an experimental and a control gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 37 publications
0
31
0
3
Order By: Relevance
“…Table 4 identifies the quality appraisal according to the JBI criteria [34,35]. Besides double blindness, three RCTs met all the other JBI criteria [46][47][48]. Additionally, one RCT could also not complete its follow-up assessment [45].…”
Section: Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Table 4 identifies the quality appraisal according to the JBI criteria [34,35]. Besides double blindness, three RCTs met all the other JBI criteria [46][47][48]. Additionally, one RCT could also not complete its follow-up assessment [45].…”
Section: Methodological Qualitymentioning
confidence: 99%
“…With regard to the study design, four RCTs [45][46][47][48], six quasi-experimental studies [28,[49][50][51][52][53] and one cohort study [54] were included. Four studies were conducted in Europe, three studies in North America and four studies in Asia.…”
Section: Article Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Other small feasibility studies have suggested that education interventions may oral health outcomes in SMI (e.g. plaque) when combined with behavioural change techniques (43). Little is known about the effectiveness of such interventions when rolled out in routine clinical practice, and further research is required in this area.…”
Section: Discussionmentioning
confidence: 99%